Women’s Political Representation in Post-Soviet Republics: Parliamentary Elections in Georgia and Abkhazia - Connolly, Eileen; Ó Beacháin Stefańczak, Karolina (Studies of Transition States and Societies, 2015)
The post-Soviet republics, outside the EU, have a comparatively poor record on women’s parliamentary representation. This has been blamed on the negative legacy of the Soviet system on contemporary gender relations, the complex relationship between the electoral and party systems and on-going political instability. An aspect of this instability is the emergence of de facto states within the internationally recognised boundaries of the former Soviet republics. Research on this region has also underlined the importance of in-depth studies of women representation in the form of single country case studies that have the capacity to tease out these sets of relationships. In this context examining both the ‘parent’ and the ‘de facto’ state allows the trajectory of the gender dimension of the political system to be examined comparatively in two political entities that share a recent political, economic and social history. As a contribution to this debate this paper examines the gender dimensions of two parliamentary contests in 2012, one in the de facto state of Abkhazia and the other in its parent state of Georgia, as a means of analysing the factors that explain the level of women’s formal political representation in these states.